On the Hardy-Littlewood maximal theorem - Shinji Yamashita (International Journal of Mathematics and Mathematical Sciences, 1982)
The Hardy-Littlewood maximal theorem is extended to functions of class PL in the sense of E. F. Beckenbach and T. Radó, with a more precise expression of the absolute constant in the inequality. As applications we deduce some results on hyperbolic Hardy classes in terms of the non-Euclidean hyperbolic distance in the unit disk.